Replacement heifers-Health program - Avery, T.B. (Kansas Agricultural Experiment Station, 2012)
Common disease causing agents are identified and a sample replacement heifer health program is presented. Written objectives are useful for evaluation of heifer rearing.
Keywords: Dairy; Replacement heifers; Colostrum; Immunoglobin